Analisis Strategi Pengembangan Usaha - Pratama, Aldiansyah; Sutisna, Ma’mun (POLITEKNIK NEGERI BANDUNG, 2015)
In running business poultry broiler, Rancamaya Farm faces many obstacles. Especially is not being able to meet all demand that there are (excess demand). The demand for chicken broiler currently reached 400.783, can be met by Rancamaya Farm is a 288.194. Along with the high education and people's income, then the demand for chicken broiler will progressively increase. This led to opportunities developed farms will increase anyway. The purpose of this research is to analyze the internal and external factors Rancamaya Farm as well as formulate strategies in developing his business. This research uses the qualitative method, as for the quantitative of with regard to internal factors (IFE) matrix, external factors (EFE) Matrix and internal-external (IE). After that, it was back in the analysis using the matrix Strength, Weakness, Opportunity and Threat (SWOT) and architecture strategy. Respondents used in these studies amounted to 7 persons, with consideration of the respondents understand the external and internal condition of the company. The results of this research indicate that the position is located in Rancamaya Farm II which gives recommendations to grow and develop. The strategy that best suits your Rancamaya Farm is a strategy of intensive (market penetration, market development, and product development) or integrative (integration, integration of the back, and the horizontal integration). The results of the SWOT analysis produces 8 business strategic alternatives for Rancamaya Farm which is then poured into 18 work program needs to be done within a period of five years.